United by Sports? Key Factors affecting Sports Participation in a Sports-based Initiative to Promote Social Integration in Segregated Communities - Anna Boemmel; Matthias Buser; Thomas Persson (Current Issues in Sport Science)
Introduction Sweden's society has become ethnically diverse, yet social exclusion and segregation remain prevalent problems, particularly in employment, housing, and education (Dahlstedt & Ekholm, 2018). Acknowledging this challenge, the Swedish government, the Swedish Sports Confederation, and sports organizations have invested in sports to promote integration. Sports for integration initiatives are perceived as a tool for enhancing social integration, physical activity, and social capital in segregated cities (Agergaard, 2018). Regular participation is essential for achieving these goals, making it crucial to understand why individuals participate or not in such initiatives and develop social capital (Flensner et al., 2021). While previous research investigated structural and sociocultural engagement boundaries, few studies examine specific program factors that influence participants' willingness to engage, particularly from their own perspectives. This study addresses this gap by investigating the key facilitators and barriers within a sports-based program leading to social integration and the development of social capital among participants from various backgrounds in a highly segregated Swedish city.